Redesigning single use to reuse: Identifying opportunities for surgical instrument sets - Dhondt, Kaat; Harding, Charlotte; Watts, Regan; De Win, Gunter; Du Bois, Els (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
<span class="NormalTextRun SCXW58737630 BCX0" data-ccp-charstyle="PLATE - Text Zchn" data-ccp-charstyle-defn=""ObjectId":"82a6f845-c61c-59d0-b695-5a9e4165d45a|1","ClassId":1073872969,"Properties":[469777841,"Arial",469777842,"Times New Roman",469777843,"SimSun",469777844,"Arial",469769226,"Arial,Times New Roman",268442635,"20",469775450,"PLATE - Text Zchn",201340122,"1",134233614,"true",469778129,"PLATE-TextZchn",335572020,"1",134231262,"true",469777929,"PLATE - Text",469778324,"Default Paragraph Font"]" data-ccp-charstyle-linked-defn=""ObjectId":"649369cc-e27a-5483-b40f-b88b65e3d7e3|1","ClassId":1073872969,"Properties":[469777841,"Arial",469777842,"Times New Roman",469777844,"Arial",469769226,"Arial",268442635,"20",469777843,"SimSun",469775450,"PLATE - Text",201340122,"2",134234082,"true",134233614,"true",469778129,"PLATE-Text",335572020,"1",335551550,"6",335551620,"6",469777929,"PLATE - Text Zchn",469778324,"Normal"]">Hospitals have a significant impact on the environment due to their size, energy-intensive processes, consumption of resources and waste generation. A trend of increased reusable products usage and so re-sterilized products is becoming visible. Nevertheless, reusable products have to compete with the added values of single use regarding convenience, effort and costs. Although the concept of reusable sterile surgical instrument sets seems valuable to reduce resource consumption compared to single-use instruments, their use is threatened by multiple inefficiencies. This case study aims to understand why the sterile sets usage is not optimal, what the consequences are for the various departments, what journey they take within the hospital, and how communication occurs regarding these sets. Observations and in-depth interviews were conducted in operation rooms, central sterilization department and the healthcare logistics department of a large sized university hospital. This led to a roadmap of the sterile surgical instrument sets within the hospital through each department involved. Using the roadmap, several critical points are discussed to design optimal reuse contexts in hospitals. In sum, we found that sets are often incomplete due to (i) a lack of turnover time for checking completeness, (ii) difficulty of recognizing specific instruments based on their name, (iii) lack of a good communication system to communicate incompleteness. Additional unwanted waste is created due to (iv) extra sets that are opened as a precaution for missing instruments, (v) unused instruments are thrown away or re-sterilized, (vi) broken sterility due to storage problems, which requires repackaging and re-sterilization.